In-silico Virtual Screening and ADMET Study to Find Novel Neuraminidase N1 Inhibitors Extended to the 150-Cavity - Ashraf Ahmed Ali Abdalsalam (Journal of Applied Pharmaceutical Science, 2017)
Neuraminidase (NA) is the major surface protein of the influenza virus. It extracellularly acts by cleaving the terminal neuraminic acid from cellular receptors recognized by the Hemagglutinin. Then, it facilitates the release of newly formed visions from the host cell surface to the neighboring cells, thereby facilitating the spread of the virus. A 150-cavity adjacent to the active conservative site is possessed by the group-1 neuraminidase, thereby rendering conformational change from open to close form when the ligand binds to the enzyme. In the present study, author reported an in silico virtual screening and docking analysis for potential neuraminidase inhibitors of various ligands obtained from the ZINC database using Autodock Vina against the 3TI6 protein. Analysis of 850 screened ligands reveal that five compounds with free binding energies of -11.2, -10.9, -10.4, -10.4, and -10.1 kcal/mol (ZINC03260201, ZINC09153352, ZINC09460395, ZINC13128611, and ZINC20605436, respectively) showed interaction with the protein at the known active site, as well as with the 150-cavity creating a stronger interaction between the ligand and the protein. Furthermore, lower binding energy is exhibited compared with the co-crystallized drug oseltamivir. In silico absorption, distribution, metabolism, and excretion (ADMET) prediction revealed that best compounds show comparative results with oseltamivir. Novel compounds interacting with the 150-cavity were successfully identified using this approach; such compounds could serve as a potential lead compound for developing a new anti-neuraminidase drug.
Keywords: Virtual screening, H1N1, Oseltamivir, Neuraminidase inhibitor, ZINC database.